Fatal Measles Virus Infection After Rituximab-Containing Chemotherapy in a Previously Vaccinated Patient. (1st November 2018) - Jent, Philipp; Trippel, Mafalda; Frey, Manuel; Pöllinger, Alexander; Berezowska, Sabina; Langer, Rupert; Furrer, Hansjakob; Béguelin, Charles
Abstract: We report the case of a young patient treated with rituximab-containing chemotherapy who was infected with measles despite previous vaccination. Treatment with vitamin A, ribavirin, and immunoglobulins was started; nevertheless he developed severe pneumonitis and deceased. Broad vaccination coverage is crucial in protecting vulnerable subjects.